A trade-off between thickness and length in the zebra finch sperm mid-piece. Issue 1883 (25th July 2018) - Mendonca, Tania; Birkhead, Tim R.; Cadby, Ashley J.; Forstmeier, Wolfgang; Hemmings, Nicola
Abstract : The sperm mid-piece has traditionally been considered to be the engine that powers sperm. Larger mid-pieces have therefore been assumed to provide greater energetic capacity. However, in the zebra finch Taeniopygia guttata, a recent study showed a surprising negative relationship between mid-piece length and sperm energy content. Using a multi-dimensional approach to study mid-piece structure, we tested whether this unexpected relationship can be explained by a trade-off between mid-piece length and mid-piece thickness and/or cristae density inside the mitochondrial helix. We used selective plane illumination microscopy to study mid-piece structure from three-dimensional images of zebra finch sperm and used high-resolution transmission electron microscopy to quantify mitochondrial density. Contrary to the assumption that longer mid-pieces are larger and therefore produce or contain a greater amount of energy, our results indicate that the amount of mitochondrial material is consistent across mid-pieces of varying lengths, and longer mid-pieces are simply proportionately 'thinner'.